Features of integrin subunit β4 expression depending on clinical and morphological parameters of breast cancer - M. V. Zavyalova; G. A. Kuznetsov; E. S. Grigorieva; L. A. Tashireva; A. V. Zavyalov; V. E. Popova; V. V. Alifanov; D. S. Pismenny; E. S. Andryukhova; V. M. Perelmuter (Бюллетень сибирской медицины)
Aim. To study the features of the expression of the integrin subunit β4 in primary tumor tissue depending on the clinical and morphological parameters of breast cancer. Materials and methods. We examined biopsy samples from 49 patients with T1–4N0–3M0 breast cancer; the median age was 51.0 [44.0; 60.0] years. Patients did not receive neoadjuvant therapy. Surgical intervention involved resection of the mammary gland with axillary lymph node dissection or radical mastectomy. The expression of markers of estrogen receptor, progesterone receptor, c-erB-2 (Her2/neu), Ki67, CD104 (integrin subunit β4) was assessed using immunohistochemistry. Statistical processing of the results was carried out using the Statisctica 10.0 software package. Results. In the group of patients with N3 degree, cases with positive cytoplasmic/membrane colocalization of integrin subunit β4 expression were more frequently detected (45%), compared with observations where no such expression was found (8%; p = 0.002). Conclusion. Positive cytoplasmic/membrane colocalization of integrin subunit β4 expression is associated with the prevalence of lymphatic metastasis, which corresponds to N3 degree.